Impact of Extraction Conditions on Resveratrol Content and Antioxidant Properties of Japanese Knotweed Extracts - Małgorzata Olszowy-Tomczyk; Dorota Wianowska (Applied Sciences)
Due to its health-promoting properties, resveratrol is one of the most desirable compounds in many industries. Hence, this work focused on finding the conditions of its extraction from Japanese knotweed which could be used on an industrial scale to obtain extracts with the best antioxidant properties. The contribution of polyphenolics to the activity of the obtained isolates was also assessed in this study. Ultrasound-assisted solvent extraction was used to prepare extracts in various solvents under conditions differing in extraction time, temperature, and ultrasound frequency. The extracts were tested for their ability to neutralize radicals and reduce metal ions. It was shown that although the best extractant was the same water–alcohol mixture, the optimal conditions for the extraction of resveratrol and polyphenols were different: 10 min, 50 °C and 80 kHz for resveratrol (for which the highest contents of resveratrol equals 0.91 mg/g was obtained) and 20 min, 25 °C and 37 kHz for polyphenolics (for which the total phenolic content equals 31.28 mg of gallic acid/g was determined) Under the latter conditions, one of the best antioxidant activities was also obtained. The results confirm that Japanese knotweed, despite its bad reputation in Europe as a very invasive species, can be used as a source of sought-after resveratrol and polyphenols.